PENINGKATAN LITERASI MEMBACA PADA SISWA SEKOLAH DASAR DI SD BORNEO INDAH MARJAYA MELALUI STRATEGI MEMBACA TERPADU: ANALISIS TEORI KONTRUKTIVISME - Amin Johari; Cendana, Wiputra (Journal of Practice Learning and Educational Development, 2026)
This research aims to analyze an integrated reading strategy based on constructivist theory to improve reading literacy among elementary school students at SD Borneo Indah Marjaya. The background of this research is based on the still low reading literacy skills of elementary school students, as shown by national and local data. The method used is a literature review of 10 recent scientific sources (5 journals and 5 books) that discuss reading strategies and constructivist learning theory. The study results show that an integrated reading strategy involving reading, writing, listening, and speaking skills can enhance students' reading comprehension. This strategy is also in line with constructivist theory, where learning occurs actively thru direct experiences and social interactions. The implementation of this strategy at SD Borneo Indah Marjaya is considered relevant and potentially capable of strengthening students' literacy skills if supported by teacher training, the availability of contextual reading materials, and support from the school and family environment. Thus, the integrated reading strategy based on constructivism can be an innovative solution in literacy education at the elementary school level.